Expressions of ezrin, ERK, STAT3, and AKT in tongue cancer and association with tumor characteristics and patient survival. Issue 4 (13th April 2020) - Noi, Masaharu; Mukaisho, Ken‐ichi; Murakami, Shoko; Koshinuma, Shinya; Machida, Yoshisato; Yamori, Masashi; Nakayama, Takahisa; Ogawa, Takao; Nakata, Yusuke; Shimizu, Takeshi; Yamamoto, Gaku; Sugihara, Hiroyuki
Abstract: Background: Ezrin, ERK, STAT3, and AKT are proteins that are overexpressed in various types of cancer, although their expressions in tongue cancer has received less focus. This study aimed to address associations between the expression levels of these proteins and with characteristics of the tumor and patient survival. Methods: We performed immunohistochemical staining of ezrin, ERK, STAT3, and AKT in tumors from patients with tongue carcinoma in situ (CIS, n = 17) and tongue squamous cell carcinoma (SCC, n = 46). Statistical differences between the SCC versus the CIS cohorts were estimated by calculations of bivariate odds ratios of low versus high expression of the proteins. Fisher's exact tests were used to appraise interassociations between the proteins, as well as expression levels versus patient and tumor characteristics. Survival based on Kaplan–Meier statistics in combination log‐rank tests were used to address potential effects of the patient and tumor characteristics versus 5‐year survival rate. Results: The relative high: low expression of all four proteins in the two cohorts differed, and particularly ERK was markedly overexpressed in the SCC versus the CIS cohort (odds ratio = 45.3, p < .01). The relative high: low expression each protein versus patient and tumor characteristics; showed associations between AKT expression and T stage ( p = .002) plus node metastases ( p = .12), and between ERK expression and drinking ( p = .01) and smoking history ( p = .01). There was no significant difference observed between ERK and the three other molecules, nor any significant difference between the degree of expression of each protein and the 5‐year disease‐specific survival rate. Conclusion: Ezrin, ERK, STAT3, and AKT appear to be involved in the progress from carcinoma in situ in the tongue into squamous cell carcinoma. ERK in particular is overexpressed, suggesting that ERK may be a novel therapeutic target for preventing tongue cancer.